Essential Nutrient and Trace Element Foliar Resorption of Two Co-Existing Nothofagus Species Grown Under Different Environmental Conditions in Southern Patagonia - Bahamonde, Héctor Alejandro; Fernández, Victoria; Gyenge, Javier; Mattenet, Francisco Javier; Peri, Pablo Luis (Frontiers Media, 2020)
Nutrient resorption is crucial for mineral element conservation and efficiency of forest species, but knowledge on its significance and the mechanisms involved is still limited for most species and habitats. Focusing on the harsh conditions for plant growth and survival of southern Patagonia, a field study for comparing the rate of foliar resorption of macro-, micro-nutrients, and trace elements in coexisting Nothofagus pumilio and Nothofagus antarctica forests was performed. Forests located in three contrasting productivity sites (with different soil and climatic conditions) were selected, and mature, functional versus senescent leaves of both species were collected at two different dates of the growing season. Macro- (N, P, Ca, K, S, and Mg), micronutrients (B, Cu, Fe, Mn, Zn, and Ni), and trace elements (Al, Li, Pb, Rb, Sr, Ti, and Tl) were determined in foliar tissues. The mineral element concentrations of mature and senescent leaves were used for calculating the nutrient resorption efficiency (NuR). In general, and making an average of all sites and species, macro-nutrient resorption showed a decreasing trend for N > S = K > P > Mg, being Ca the only macro-nutrient with negative values (i.e., no resorption). Resorption of the majority of the elements did not vary between species in any of the evaluated sites. Variation across sites in nutrient resorption efficiency for most macronutrients, some micronutrients, and trace elements was observed for N. antarctica, whereas N. pumilio had a similar NuR for all experimental sites. On the other hand, regardless of the site or the species, some elements were not resorbed (e.g., B, Cu, Fe, Mn, Al, and Ti). It is concluded that both Nothofagus species performed similarly concerning their nutrient conservation strategy, when coexisting in the same mixed forest. However, no evidence was gained for an increased rate of foliar NuR in association with the sites subjected to more limiting soil and climatic conditions for plant growth.